PERAN PEMERINTAH TERHADAP FENOMENA PENGGUNAAN BAHASA ASING DI SEKOLAH - Susanti, Dewi Indah; Hamid, Slamet (Lentera: Jurnal Ilmiah Kependidikan, 2018)
The use of Indonesian as a language of unity is currently experiencing a shift in value. A number of international standard schools (SBI) place foreign languages as the language of education. This is contrary to Article 33 of Law Number 20 of 2003 concerning the National Education System and Article 29 of Law Number 24 of 2009 concerning Flags, Language and State Symbols and National Anthems. In both laws, the language of instruction in national education is Indonesian, so a number of SBIs should prioritize the use of Indonesian, not foreign languages such as English. This study aims to determine the extent of the role of the government in addressing the use of foreign languages in schools. This research method uses observation methods and literature